Some Directions of using the Forensic Odorology in the Field of the Fixing Evidences in the Pre-Trial Proceedings in Ukraine - Zarosylo, Volodymyr O.; Yarovoi, Tykhon S.; Grokholskyi, Volodymyr L.; Timashov, Victor O.; Padalka, Rostislav K. (International Journal of Criminology and Sociology, 2022)
All over the world, the issue of detecting crimes committed is the main task of the state and its law enforcement agencies. The detection of crimes and the prosecution of those who committed them are in most cases based on evidence gathered by law enforcement officers. The issue of evidence is also quite debatable, because the legislation of different countries perceives different aspects of evidence and the evidence itself. The article covers the issue of individual issues related to obtaining evidence with the help of specially trained dogs. These forms and methods were used by Ukrainian law enforcement officials during their stay in the international peacekeeping mission in Kosovo. Currently, some evidence-gathering issues can be used in the process of investigating and prosecuting criminals with trained dogs. However, this area is not widely used, as there are a number of both practical and regulatory, as well as legislative problems. This direction in the activities of the police and other law enforcement agencies is called forensic odorology. The issue of using dogs in the process of detecting and investigating crimes is quite controversial and they are used differently in different countries.